2016
DOI: 10.1118/1.4966134
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of linear interpolation models for iterative CT reconstruction

Abstract: Purpose: Recent reports indicate that model-based iterative reconstruction methods may improve image quality in computed tomography (CT). One difficulty with these methods is the number of options available to implement them, including the selection of the forward projection model and the penalty term. Currently, the literature is fairly scarce in terms of guidance regarding this selection step, whereas these options impact image quality. Here, the authors investigate the merits of three forward projection mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 92 publications
0
20
0
Order By: Relevance
“…For example, a 1 mm voxel close to the source may present a 2.5 by 2.5 mm footprint on the detector, which (assuming 1 mm detector pixels) would require nine SSM entries in that view. See Hahn et al (38) for a recent discussion on forward projectors.…”
Section: E Experimentsmentioning
confidence: 99%
“…For example, a 1 mm voxel close to the source may present a 2.5 by 2.5 mm footprint on the detector, which (assuming 1 mm detector pixels) would require nine SSM entries in that view. See Hahn et al (38) for a recent discussion on forward projectors.…”
Section: E Experimentsmentioning
confidence: 99%
“…Nevertheless, the relative error introduced by both methods varies with the projection angle for typical CBCT geometries and the weights are again relative. Another study by Hahn et al . compared DD, the Joseph method and bi‐linear interpolation.…”
Section: Theorymentioning
confidence: 99%
“…3 Nevertheless, the relative error introduced by both methods varies with the projection angle for typical CBCT geometries and the weights are again relative. Another study by Hahn et al 30 compared DD, the Joseph method and bi-linear interpolation. It demonstrated that DD was superior to the Joseph method, at a greater computational cost, and a choice between the two may be based on the acquisition parameters.…”
Section: A System Matrix Modelsmentioning
confidence: 99%
“…Furthermore, Tang et al provided a comparison with total variation . As they can be designed in many different ways, forward projection models for iterative CT reconstruction have also been given a lot of attention in terms of efficiency and impact on image quality . In the same context, the importance of statistical weights in the data fidelity term was examined using both model observers and human readers…”
Section: Introductionmentioning
confidence: 99%
“…16 As they can be designed in many different ways, forward projection models for iterative CT reconstruction have also been given a lot of attention in terms of efficiency and impact on image quality. [17][18][19][20][21][22][23][24] In the same context, the importance of statistical weights in the data fidelity term was examined using both model observers 25 and human readers. 26 In this paper, we are interested in the non-negativity constraint.…”
Section: Introductionmentioning
confidence: 99%